The Design of a Cracker Dough Cutting Machine Using an Effective And Efficient Roll Cutting Setter For Home Industry Scale - Singgeh Adi Wibowo; Ali Akbar (Universitas Muhammadiyah Sidoarjo, 2021)
The design aims to produce mass cracker production on a homa scale industry that is effective and efficient i order to meet consumption needs. The cutting machine has on a 50cm length of aluminium strip plate, a roll knife made of stainless stell, 1,5mm thick, 45mm diameter, 5mm middle axle hole, with letter L shape support. With 12 knives the roll has a distance of 4cm. Testing on a thick dough of 1-1,5mm width 46cm square with the help of a 10mm thick pvc mattress 50cm wide square using a stopper right and left in the shape of an angle of 3mm thick iron plate the work process of scratching a roll knife into the dough on the mat with a reference to the stopper of longitudinal and transverse movements for effective and efficient results, testing five times gets an average time of 00:49 seconds in the previous test while in the renewable machines it gets an average time of 00:22seconds. So the results of the analysis can be said to be effective and have more efficiency than previous machines.